Gastrointestinal failure score alone and in combination with SOFA score in the assessment of the critically ill patients - Mayada Mahmoud Hussein; Amna Metwaly; Lamiaa Hamid; Nashwa Abed (Cairo : Mayada Mahmoud Hussein, 2010)
Our study is to evaluate the GIF score in our Egyptian intensive care units regarding validity and impact on mortality and comparing this with the SOFA score and to describe the prevalence of food intolerance and intra-abdominal hypertension among ICU patients and their impact on mortality
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Failure; Gastrointestinal; Hypertension